Waveform analysis of shank loaded wearable resistance during sprint running acceleration. Issue 17 (2nd September 2021) - Feser, Erin H; Neville, Jono; Bezodis, Neil; Macadam, Paul; Uthoff, Aaron M.; Nagahara, Ryu; Tinwala, Farhan; Cronin, John B.
ABSTRACT: Lower-limb wearable resistance (WR) provides a specific and targeted overload to the musculature involved in sprint running, however, it is unknown if greater impact forces occur with the additional limb mass. This study compared the contact times and ground reaction force waveforms between sprint running with no load and 2% body mass (BM) shank-positioned WR over 30 m. Fifteen male university-level sprint specialists completed two maximum effort sprints with each condition in a randomized order. Sprint running with shank WR resulted in trivial changes to contact times at 5 m, 10 m, and 20 m (effect size [ES] = <0.20, p > 0.05) and a small, significant increase to contact time at 30 m by 1.94% (ES = 0.25, p = 0.03). Significant differences in ground reaction force between unloaded and shank loaded sprint running were limited to the anterior-posterior direction and occurred between 20% and 30% of ground contact at 10 m, 20 m, and 30 m. Shank WR did not result in greater magnitudes of horizontal or vertical forces during the initial impact portion of ground contact. Practitioners can prescribe shank WR training with loads ≤2% BM without concern for increased risk of injurious impact forces.